2017
DOI: 10.1177/2051570717738694
|View full text |Cite
|
Sign up to set email alerts
|

The influence of consumer confidence on inter-format competition: An analysis based on the French Consumer Confidence Index

Abstract: The multiple store formats (Drive, hypermarkets, hard discount stores, convenience stores) tend to strengthen inter-format competition in addition to the intra-format competition. Thus, when he or she has to shop, the consumer is now facing several solutions. Research in marketing was much interested in determining the choice of store formats using variables such as the composition of the assortment, price, and sales promotions. More recently, analysts have raised the issue of whether the economic context coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The effect of consumer expectation on the consumption is examined by Oduh, Oduh and Ekeocha (2012) for Nigerian economy between 2009-2011 and it was found that the variables having the greatest effect on consumption are the exchange rate and consumer confidence index. Similarly, Ngobo and Ingarao (2017) analyzed the impact of the consumer confidence index for France which is in the developed country category, and they stated that the increase or decreases in the consumer confidence index has asymmetric and nonlinear effect on expenses.…”
Section: Related Literaturementioning
confidence: 99%
“…The effect of consumer expectation on the consumption is examined by Oduh, Oduh and Ekeocha (2012) for Nigerian economy between 2009-2011 and it was found that the variables having the greatest effect on consumption are the exchange rate and consumer confidence index. Similarly, Ngobo and Ingarao (2017) analyzed the impact of the consumer confidence index for France which is in the developed country category, and they stated that the increase or decreases in the consumer confidence index has asymmetric and nonlinear effect on expenses.…”
Section: Related Literaturementioning
confidence: 99%